Effects of customized consumption feedback on energy efficient behaviour in low-income households. (1st September 2016) - Podgornik, Ales; Sucic, Boris; Blazic, Bostjan
Abstract: Smart metering and various consumption-feedback systems can be used as applicable technology to encourage end-use energy efficiency in the residential sector. Many studies have demonstrated the positive influence of socially contextualized feedback on the energy consumption of households, but not many such studies dealt with the specifics of low-income households. This paper evaluates the effect of customized consumption feedback and other information interactions on energy-behaviour patterns and energy savings in low-income households. The experimentation process was accompanied by an interactive awareness campaign, with the emphasis being on a proper understanding of the consumption feedback and other complementary energy services provided to low-income households. The feedback actions were customized to tackle the recognised needs of each specific target household, considering both the social aspects and the typology of the dwelling. The results clearly confirmed the importance of customized information and efficiency indicators for specific household groups, with a potential to increase knowledge and develop awareness with respect to established habits and their relevance to energy behaviour. Highlights: Two consumption feedback approaches in low-income households were examined. Consumption feedback experiment was supported by interactive awareness campaign. Combining several approaches (audit, advice and feedback) was especially effective. Individualized feedback results in 22–27% reduction in electricity use. Raising energy awareness is a key element for successful energy behaviour change.